The Form is Not a Proper Part in Aristotle's Metaphysics Z.17, 1041b11–33. (8th August 2018) - Rotkale, Liva
When Aristotle argues at the Metaphysics Z.17, 1041b11–33 that a whole, which is not a heap, contains 'something else', i.e. the form, besides the elements, it is not clear whether or not the form is a proper part of the whole. I defend the claim that the form is not a proper part within the context of the relevant passage, since the whole is divided into elements, not into elements and the form. Different divisions determine different senses of 'part', and thus the form is not a part in the same sense as the elements are parts. I object to Koslicki's (2006 ) interpretation, according to which the form is a proper part along the elements in a single sense of 'part', although she insists that the form and the elements belong to different categories. I argue that Koslicki's reading involves a category mistake, i.e. the conjunction of items that do not belong to the same category (Goldwater 2018 ). Since for Aristotle parthood presupposes some kind of similarity of parts, the conjunction of form and elements requires treating these items as somehow belonging to the same category, e.g. 'being', but no such category exists.